2016
DOI: 10.1002/celc.201600061
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Spinel Oxides/N‐Doped Reduced Graphene Oxide as Highly‐Active Bifunctional Electrocatalysts for Oxygen Reduction/Evolution Reactions

Abstract: A series of Co3O4–MnCo2O4/N‐doped reduced graphene oxide (CMO/N‐rGO) electrocatalysts with different N‐rGO content were developed by using a two‐step synthetic method. The electrocatalysts were characterized by X‐ray diffraction, scanning electron microscopy/transmission electron microscopy, and X‐ray photoelectron spectroscopy. Their catalytic activities toward the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) were evaluated by linear‐sweep voltammetry (LSV) in an alkaline electrolyte. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 68 publications
(86 reference statements)
1
27
0
Order By: Relevance
“…It is also worth mentioning that ORR onset potential at Carb‐IL is comparable or positive compared to onset potential values observed at carbon materials with noble metals such as palladium‐graphitic carbon nitride nanocomposite (0.9 V), Ag‐MWCNT (0.8 V), Au‐graphene (0.71 V) and metals such as cobalt‐nitrogen doped carbon (0.86 V) and cobalt‐nitrogen doped reduced graphene oxide (0.9 V) ,. ORR activity of easily prepared Carb‐IL is better or similar compared to series of nanocomposite Co 3 O 4 ‐MnCo 2 O 4 /N‐doped reduced graphene oxide electrocatalysts . Carbon materials prepared by carbonization of other ILs showed similar properties in terms of the ORR onset potential and mechanism.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…It is also worth mentioning that ORR onset potential at Carb‐IL is comparable or positive compared to onset potential values observed at carbon materials with noble metals such as palladium‐graphitic carbon nitride nanocomposite (0.9 V), Ag‐MWCNT (0.8 V), Au‐graphene (0.71 V) and metals such as cobalt‐nitrogen doped carbon (0.86 V) and cobalt‐nitrogen doped reduced graphene oxide (0.9 V) ,. ORR activity of easily prepared Carb‐IL is better or similar compared to series of nanocomposite Co 3 O 4 ‐MnCo 2 O 4 /N‐doped reduced graphene oxide electrocatalysts . Carbon materials prepared by carbonization of other ILs showed similar properties in terms of the ORR onset potential and mechanism.…”
Section: Resultsmentioning
confidence: 82%
“…Number of electrons obtained for HTC suggests co‐existence of two‐ and four‐electron ORR pathway at this material . Electrocatalysts efficiency for the ORR, i. e., the amount of HO 2 − generated is, to a great extent, governed by structure and thickness of the active layer.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The Co 3 O 4 nanocrystals are also potential alternates for novel metal Pt to catalyze ORR, but the activity and stability are still inferior to commercial Pt/C in fuel cell operation . To enhance the ORR electrocatalytic performance of Co 3 O 4 , various approaches have been adopted, such as crystal‐plane‐ or morphology‐controlled, size‐controlled, electroconductivity‐enhanced and doping . Nevertheless, to the best of our knowledge, the effect of electrocatalytic activity for ORR only caused by the shift on crystal planes of Co 3 O 4 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…48 Moreover, metallic doping of cobalt and iron based spinel with for example Ni, Mn, Cu etc, were studied for catalytic performance as well. 10,49,50 It was reported that for MFe2O4 (where M= Mn, Cu, Ni, Co) follows a trend of Co>Cu>Ni>Mn for OER activity. 16 Similarly, for cobalt based spinels, OER performance has increased with doping Ni, Cu, Li except Mn, 51 Overall, bimetallic spinel oxides proven to have better OER performance than single metal spinel M3O4 due to the synergy created using different metals ions as they might have an impact in optimising adsorption energy.…”
Section: Spinelsmentioning
confidence: 99%